Correlation between retinal sensitivity and retinal vascular perfusion after idiopathic epiretinal membrane peeling - Nicolai, Michele; Franceschi, Alessandro; De Turris, Serena; Rosati, Alessandro; Carpenè, Maria Jolanda; Danieli, Luca; Lassandro, Nicola Vito; Pelliccioni, Paolo; Lupidi, Marco; Mariotti, Cesare (European journal of ophthalmology, 2024)
To evaluate the correlations between anatomical and functional changes after idiopathic epiretinal membrane (iERM) surgery. In this prospective, observational, single-center study, consecutive patients who underwent iERM peeling were enrolled. Reported data were pre- and postoperative best-corrected visual acuity (BCVA), retinal sensitivity (RS) and fixation stability values on microperimetry, structural macular features on SD-OCT and OCTA. RS of foveal and parafoveal area was analysed and two sub-groups were identified whether RS improved or remained unchanged/worsened after surgery; consequently, vascular perfusion density (VPD) of the same area was studied. Twenty-nine eyes of 29 patients were examined. The post-operative improvement in terms of BCVA, RS and fixation within the central 4 degrees was significant (p < 0.001, p < 0.001, p = 0.001), as well as the foveal thickness and macular volume change/reduction (p < 0.001). The pre-operative superficial VPD, choriocapillaris VPD and capillary free zone (CFZ) area were significantly reduced compared to the fellow healthy eye (p = 0.001, p = 0.02, p < 0.001). Choriocapillaris VPD showed a statistically significant increase after surgery (p < 0.02). Superficial, deep and choriocapillaris VPD of the improved RS group showed a significant increase both in foveal (p = 0.03, p = 0.03, p = 0.01) and parafoveal areas (p = 0.01, p = 0.03, p = 0.001). We reported a higher VPD in the retinal area that experienced a retinal sensitivity improvement 6 months after ERM surgery. This result objectifies the tight bond between visual function and retinal perfusion in ERM patients.